Gene expression of paracoccidioides virulence factors after interaction with macrophages and fibroblasts - Braz, Jaqueline Derissi [UNESP]; Sardi, Janaina de Cássia Orlandi [UNESP]; Pitangui, Nayla de Souza [UNESP]; Voltan, Aline Raquel [UNESP]; Almeida, Ana Marisa Fusco [UNESP]; Giannini, Maria José Soares Mendes [UNESP] (FapUNIFESP (SciELO), 2021)
Paracoccidioidomycosis (PCM) is a systemic mycosis with high prevalence in Latin America that is caused by thermodimorphic fungal species of the Paracoccidioides genus. In this study, we used quantitative PCR (qPCR) to investigate the expression of genes related to the virulence of Paracoccidioides brasiliensis (Pb18) and P. lutzii (Pb01) strains in their mycelial (M) and yeast (Y) forms after contact with alveolar macrophages (AMJ2-C11 cell line) and fibroblasts (MRC-5 cell line). The selected genes were those coding for 43 kDa glycoprotein (gp43), enolase, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), 14-3-3 protein (30 kDa), phospholipase, and aspartyl protease. In the Pb18 M form, the aspartyl protease gene showed the highest expression among all genes tested, both before and after infection of host cells. In the Pb18 Y form after macrophage infection, the 14-3-3 gene showed the highest expression among all genes tested, followed by the phospholipase and gp43 genes, and their expression was 50-fold, 10-fold, and 6-fold higher, respectively, than that in the M form. After fibroblast infection with the Pb18 Y form, the 14-3-3 gene showed the highest expression, followed by the phospholipase and aspartyl protease genes, and their expression was 25-fold, 10-fold, and 10-fold higher, respectively, than that in the M form. Enolase and aspartyl protease genes were expressed upon infection of both cell lines. After macrophage infection with the Pb01 Y form, the 14-3-3 gene showed the highest expression, followed by the phospholipase and aspartyl protease genes, and their expression was 18-fold, 12.5-fold, and 6-fold higher, respectively, than that in the M form. In conclusion, the data show that the expression of the genes analyzed may be upregulated upon fungus-host interaction. Therefore, these genes may be involved in the pathogenesis of paracoccidioidomycosis.
Keywords: Adhesin genes; M form; Paracoccidioides spp; Virulence factors; Y form